The use of mobile health applications in empowering self-management of type 2 diabetes: a literature review - Öcal, Pelin (The European Research Journal, 2024)
The use of mobile health applications is vital for achieving glycemic control, promoting lifestyle changes, and empowering self-management in individuals with type 2 diabetes. This literature review aims to assess the effectiveness of mobile health applications in empowering self-management among type 2 diabetes patients. A thorough search was conducted in databases like PubMed, CINAHL, Web of Science, Cochrane Library, Scopus, ULAKBIM National Database, and Medline between January 2020 and March 2023, using keywords such as "mobile health, mobile applications, type 2 diabetes, diabetes self-management, nursing." The search yielded 525 articles, out of which 34 studies in Turkish or English that evaluated the effectiveness of mobile health applications in individuals aged 18 years and above with type 2 diabetes were included in the review. Recent studies demonstrate a growing utilization of mobile health applications for the management of treatment and care in individuals with type 2 diabetes. These applications have been shown to empower self-management by promoting dietary adherence, regular blood sugar monitoring, regular physical activity, reduced medication requirements, and decreased HbA1c levels. Additionally, mobile health applications have been found to reduce face-to-face counseling time and healthcare costs. In conclusion, mobile health applications offer promising solutions for improving self-management and healthcare outcomes for individuals with type 2 diabetes. Further research and continued integration of these applications into clinical practice are essential to optimize their benefits and address the challenges faced by diabetes patients worldwide.